2008
DOI: 10.1037/0097-7403.34.3.315
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning of stimuli with nonzero initial value.

Abstract: In five experiments, rats received conditioning of either moderately attractive or moderately aversive flavors using either a strongly negative lithium chloride (LiCl) or a strongly positive Polycose as the reinforcer. In each case, testing was done with a compound of the two moderately valued stimuli to determine the amount of associative change produced by the pairing. In both within-subject and between-subjects designs, the amount of associative change was greater for a signal whose moderate value was oppos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…For example, it is likely that our rats entered our Experiment 1 with sweet taste→calorie associations already formed, as result of pre-weaning experience or as a result of consuming sugars contained in their normal 5001 maintenance chow. In fact, Rescorla (2008) provided evidence consistent with the idea that sweet orosensory CSs possess associative value prior to the beginning of experimental training. He reported that when such CSs are subject to experimental training, their “initial non-zero value” modulates the effectiveness of a US in much the same way as other types of CSs that have been given explicit training with a US.…”
Section: Resultssupporting
confidence: 69%
“…For example, it is likely that our rats entered our Experiment 1 with sweet taste→calorie associations already formed, as result of pre-weaning experience or as a result of consuming sugars contained in their normal 5001 maintenance chow. In fact, Rescorla (2008) provided evidence consistent with the idea that sweet orosensory CSs possess associative value prior to the beginning of experimental training. He reported that when such CSs are subject to experimental training, their “initial non-zero value” modulates the effectiveness of a US in much the same way as other types of CSs that have been given explicit training with a US.…”
Section: Resultssupporting
confidence: 69%
“…Our model of individual learning and decision making is directly based on research in psychology and neuroscience, which have showed that the Rescorla-Wagner learning rule, along with other closely related rules, provides a concise description of both behavioral and neural aspects of learning from rewards and punishment [ 52 , 77 , 78 ], as well as being evolutionarily robust [ 60 ]. The implementation of how preparedness and learning interacts (as competing influences at the decision stage) is based on behavioral experiments conducted in our lab [ 43 ], but other, similar, implementations are possible [ 45 , 79 , 80 ]. The implementation of observational learning ( O 1 ) was identical to individual learning, and is supported by previous behavioral [ 55 ] and neural [ 57 ] findings in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of cues in triggering automatic/habitual behaviors is well recognized in basic behavioral sciences spanning neuroscience (Knowlton, Mangels, & Squire, 1996; Yin & Knowlton, 2006a), memory (Nelson & Goodmon, 2003; Rescorla, 2008), and research on appetitive behaviors (LaBar et al, 2001). Yet, most approaches to understanding adolescent risk behavior do not incorporate cue effects and their link to habit formation.…”
Section: Introductionmentioning
confidence: 99%